Nigerian newspapers’ use of euphemism in selection and presentation of news photographs of terror acts (2018)
Selection of photographs is part of the complex process of creating the multimodal textual elements that news editors use to represent and interpret social reality. This article, guided by Aristotle’s golden mean and Halliday’s theoretical notion of metafunctions, used critical visual analysis to examine the nature of photographs that news editors of Nigerian newspapers selected and used to frame news stories about acts of terrorism by the Boko Haram sect. The pattern established through the visual analysis shows that, although the stories of terror act by the Boko Haram sect present deviant and negative social realities, news editors of the selected newspapers exercised ethical restraint by choosing images with nuanced configurations that are less likely to amplify moral panic or intensify horrid feelings. Using euphemistic photographs to tell stories about terror acts is a demonstration of ethical responsibility that has great implications for public peace especially in an African country like Nigeria with security concerns.